Analysis of Meteorological Drought Cycle Basedon Wavelet Function in Zhanjiang - ZHANG Desheng; CHEN Yafen; TAN Senming (Renmin Zhujiang)
Based on monthly rainfall data of 19 stations from 1966 to 2015 in Zhanjiang City, Guangdong Province, which is selected as the research area, this paper conducts the spatial modal decomposition of regional meteorological drought distribution by using the standardized precipitation index of 6 months and the rotated empirical orthogonal function, and calculates the drought period of different spatial modes through wavelet analysis. The results show that the spatial distribution of drought in Zhanjiang can be decomposed into 6 spatial modes. Different modes correspond to different regions. The strongest signal of the drought cycle in the region is 9.3 a and the weakest is 2.1 a, and there are 2~6 a oscillation periods in different modes, which are basically consistent with the actual drought cycle. The reason for the periodic variation of drought in Zhanjiang is related to the El Nino event. The relationship between spring rainfall and El Nino is more closely related, and the impact of El Nino on spring drought is more sustained and significant.